A representação do feminismo negro nos contos A Escrava, de Maria Firmina dos Reis, e Maria, de Conceição Evaristo - Oliveira, Maria Evelta Santos de (2024)
This work aims to investigate the way in which Black Feminism is reproduced in short stories A Escrava, by Maria Firmino do Reis, and Maria, by Conceição Evaristo. As theoretical perspective, the studies of Maria Firmina dos Reis (1887, 2009), Pierre Bourdieu (2002), Simone Beauvoir (2009), Conceição Evaristo (2009, 2010, 2016), Djamila Ribeiro (2017, 2018), among others. This is a study of review, in this sense, the methodological path used to carry out this research, was a bibliographic study with a qualitative approach. The analysis revealed that the protagonists of the stories face challenges arising from racial discrimination and gender, both in historical and contemporary aspects. The authors, Firmina dos Reis and Evaristo used literature as a tool to portray and denounce the difficulties and suffering experienced by black women. Through your narratives, they highlight the daily struggle for dignity, freedom and recognition within a society marked by structural racism and gender oppression. By confronting and challenging the stereotypes and injustices faced by protagonists, the authors contribute to the construction of a narrative that demands equality and dignity for all women, regardless of their color or social origin.